Book of Abstracts of the 21th European Conference on Eye Movements in Leicester 2022 - Victoria McGowan; Ascensión Pagán; Kevin B. Paterson; David Souto; Rudolf Groner (Bern Open Publishing, 2022)
Contents    Keynotes: Iain Gilchrist: Integrative Active Vision p 5 Ziad Hafed: A Vision for orienting in Primate Oculomotor Control Circuitry p 6 Fatema Ghasia: Miniscule Eye Movements Play a Major Role in Binocular Vision Disorders p.7 Miriam Spering: Eye Movements as a Window into Human Decision-Making p.8 Monica S. Castelhano: Explorations of how Scene Context and Previous Experience Dynamically Influence Attention and Eye Movement Guidance p.9      Symposia: Eye Tracking and the Visual Arts p.19 Eye Movements during Text Processing and Multiline Reading p.23 Unstable Fixation and Nystagmus with a Focus on the Next Generation of Researchers p.84 Eye Movements as a measure of Higher-Level Text Processing p.97 Eye Movements in Memory Processes Between Working Memory and Long-Term Memory p.178 Symposium to Honour Alexander Pollatsek's Legacy to Eye Movement Research p.204      Talks: Reading p.30 Parafoveal Processing p.36 Cinical and Applied p.39 Visual Search p.92 Eye Movement Control in Reading I & II p.104 & 116 & 225 Reading Development p.110 Decision-Making   p.122 Eye-tracking Methods p.128 Real World and Virtual Reality p.134 Chinese Reading p.185 Special Populations p.191 Visuo-motor p.195 Bilingual Reading p.201 & 217 Reading Comprehension p.219 Pupillometry p.235      Poster sessions: Attention p.44 & 139 Cognition p. 49 Visuo-Motor p.62 Memory p.145 Methods p.150 Reading p. 57 & 155 Real World p.169 Social Cognition p.173